Thymus Vulgaris Oil Nanoemulsion: Synthesis, Characterization, Antimicrobial and Anticancer Activities - Ahmed S. Doghish; Amr M. Shehabeldine; Hesham A. El-Mahdy; Mahmoud M. H. Hassanin; Abdulaziz A. Al-Askar; Samy A. Marey; Hamada AbdElgawad; Amr H. Hashem (Molecules, 2023)
Essential oil nanoemulsions have received much attention due to their biological activities. Thus, a thyme essential oil nanoemulsion (Th-nanoemulsion) was prepared using a safe and eco-friendly method. DLS and TEM were used to characterize the prepared Th-nanoemulsion. Our findings showed that the nanoemulsion was spherical and ranged in size from 20 to 55.2 nm. The micro-broth dilution experiment was used to evaluate the in vitro antibacterial activity of a Th-emulsion and the Th-nanoemulsion. The MIC50 values of the thymol nanoemulsion were 62.5 mg/mL against Escherichia coli and Klebsiella oxytoca, 250 mg/mL against Bacillus cereus, and 125 mg/mL against Staphylococcus aureus. Meanwhile, it emerged that the MIC50 values of thymol against four strains were not detected. Moreover, the Th-nanoemulsion exhibited promising antifungal activity toward A. brasiliensis and A. fumigatus, where inhibition zones and MIC50 were 20.5 ± 1.32 and 26.4 ± 1.34 mm, and 12.5 and 6.25 mg/mL, respectively. On the other hand, the Th-nanoemulsion displayed weak antifungal activity toward C. albicans where the inhibition zone was 12.0 ± 0.90 and MIC was 50 mg/mL. Also, the Th-emulsion exhibited antifungal activity, but lower than that of the Th-nanoemulsion, toward all the tested fungal strains, where MIC was in the range of 12.5–50 mg/mL. The in vitro anticancer effects of Taxol, Th-emulsion, and Th-nanoemulsion were evaluated using the standard MTT method against breast cancer (MCF-7) and hepatocellular carcinoma (HepG2). Additionally, the concentration of VEGFR-2 was measured, and the activities of caspase-8 (casp-8) and caspase-9 (casp-9) were evaluated. The cytotoxic effect was the most potent against the MCF-7 breast cancer cell line after the Th-nanoemulsion treatment (20.1 ± 0.85 µg/mL), and was 125.1 ± 5.29 µg/mL after the Th-emulsion treatment. The lowest half-maximal inhibitory concentration (IC50) value, 20.1 ± 0.85 µg/mL, was achieved when the MCF-7 cell line was treated with the Th-nanoemulsion. In addition, Th-nanoemulsion treatments on MCF-7 cells led to the highest elevations in casp-8 and casp-9 activities (0.66 ± 0.042 ng/mL and 17.8 ± 0.39 pg/mL, respectively) compared to those with Th-emulsion treatments. In comparison to that with the Th-emulsion (0.982 0.017 ng/mL), the VEGFR-2 concentration was lower with the Th-nanoemulsion treatment (0.672 ± 0.019ng/mL). In conclusion, the Th-nanoemulsion was successfully prepared and appeared in nanoform with a spherical shape according to DLS and TEM, and also exhibited antibacterial, antifungal, as well as anticancer activities.